App ImproLivre como suporte no estudo da improvisação musical livre - Evangelista, Laídia da Silva (2022)
With the objective of offering subsidies to the study of the practice of non-idiomatic improvisation of free improvisation, the research proposes an experience on the creation of an application called ImproLivre. The ImproLivre app, whose function is to play sounds and noises, while the musician/student will work on the listening process before running the app, encouraging the creative and spontaneous process as much as the study of free improvisation. The Architecture and development of the application as a backend for the Pure Data programming language. The research methodology is exploratory and qualitative, also making use of Ausubel’s learning theory. Ten survey participants will experience the application in practice and will answer a question about how the application works and about their individual views on the use of technologies in musical educational environments. Not following the research and as a conclusion, we propose a reflection on the exploration of the potential the computing can trace in the artistic and educational field, providing different directions.